Taxonomic revision of the genus Oplognathus MacLeay, 1819 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini) - Carvalho, Tamara G.; Seidel, Matthias; Grossi, Paschoal C. (European Journal of Taxonomy, 2021)
The genus Oplognathus MacLeay, 1819 is revised based on type material of two of the three described species and scattered additional material from several collections around the world. The diagnostic characters of the genus are confirmed, distinguishing it from other Brazilian Areodina mainly by: quadrangular clypeus with trilobate apex in males, rounded in females, extending beyond labrum in both sexes; mandibles with three distinct teeth; maxillae with six teeth; antenna with 10 antennomeres; 10 elytral striae; mesoventral process present; and asymmetrical parameres. The genus and all three species are redescribed, and the female of Oplognathus bahianus Ohaus, 1912 is described for the first time. We consider Oplognathus helmenreichi var. maculicollis Ohaus, 1914 an unavailable infrasubspecific taxon that is conspecific with Oplognathus helmenreichi Ohaus, 1905; its distribution is updated, and the different spelling of the specific epithet is discussed. A neotype is designated for Oplognathus kirbii MacLeay, 1819 since the holotype is currently considered lost. Additionally, an identification key and a distribution map are included.